The effect of dietary polyphenols on intestinal absorption of glucose and fructose: Relation with obesity and type 2 diabetes. Issue 4 (19th May 2019) - Loureiro, Guilherme; Martel, Fátima
ABSTRACT: Polyphenols are a group of substances present in plant-based foods such as apples and in plant-based beverages such as red wine. This review shows that polyphenols interfere with intestinal sugar transporters, modulating their function and altering glucose and fructose absorption. Inhibition of intestinal glucose and fructose absorption contributes to the effect of polyphenols in reducing postprandial glycemia, altering the apparent glycemic index of foods and decreasing body mass index. The possible implication of these findings on type 2 diabetes and obesity is a matter of growing interest, as shown by the rise on publications on this subject. Abbreviations: BBM: Brush Border Membrane; BLM: Basolateral Membrane; BMI: Body Mass Index; ECg: Epicatechin Gallate; EC: Epicatechin; EGC: Epigallocatechin; EGCg: Epigallocatechin Gallate; GLUT2: Facilitative Glucose Transporter 2; GLUT5: Facilitative Glucose Transporter 5; HFCS: High-Fructose Corn Syrup; HPLC/MS: High performance Liquid Chromatography/Mass Spectrometry; HOMA-IR: Homeostatic Model Assessment; IFD: International Diabetes Federation; LPH: Lactase Phloridzin Hydrolase; MAPK: Mitogen Activated Protein Kinase; MetS: Metabolic Syndrome; NHS I e II: Nurses' Health Study I and II; PK: Protein Kinase; SGLT-1: Sodium-Glucose Co-Transporter; T2D: Type 2 Diabetes